2005
DOI: 10.1152/japplphysiol.00532.2005
|View full text |Cite
|
Sign up to set email alerts
|

Stimulatory effect of CO2 on vagal bronchopulmonary C-fiber afferents during airway inflammation

Abstract: Stimulatory effect of CO 2 on vagal bronchopulmonary C-fiber afferents during airway inflammation. J Appl Physiol 99: 1704 -1711, 2005. First published June 30, 2005; doi:10.1152/japplphysiol.00532.2005.-This study investigated 1) whether pulmonary C fibers are activated by a transient increase in the CO 2 concentration of alveolar gas; and 2) if the CO 2 sensitivity of these afferents is altered during airway inflammation. Single-unit pulmonary C-fiber activity was recorded in anesthetized, open-chest rats. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…It is possible that this high sensitivity is related to immaturity of nerve development characterized as containing more C fibers as mentioned above. In addition, accumulated evidence has demonstrated that PCFs can be chemically stimulated by local tissue heat (46), acidification (20,24), hypercapnia (19,34), and reactive oxygen species (47). PCFs are also mechanically sensitive to increased interstitial fluid volume or pressure in the lungs and airway mucosa (39,45).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that this high sensitivity is related to immaturity of nerve development characterized as containing more C fibers as mentioned above. In addition, accumulated evidence has demonstrated that PCFs can be chemically stimulated by local tissue heat (46), acidification (20,24), hypercapnia (19,34), and reactive oxygen species (47). PCFs are also mechanically sensitive to increased interstitial fluid volume or pressure in the lungs and airway mucosa (39,45).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing alveolar CO2 concentration activates pulmonary C-fibers, particularly when inflammation is present, likely due to local decreases in pH [36]. As discussed below, TRPV1 is an acid-sensing ion channel in C-fibers.…”
Section: Drugs Targeting the Generator Potentialmentioning
confidence: 99%
“…Activation of bronchopulmonary C‐fibres results in the initiation of protective reflexes such as cough, dyspnoea, and increased cholinergic output leading to mucus secretion and bronchoconstriction to aid in the clearance of harmful substances from the airways (Coleridge & Coleridge, 1984; Lee & Pisarri, 2001). During inflammatory airway diseases, however, C‐fibre activation can become enhanced or sensitized (Lin et al 2005; Zhang et al 2008; Li & Yu, 2009). This may contribute substantively to the overall pathophysiology and symptomatology of allergic airway disease.…”
Section: Introductionmentioning
confidence: 99%